Cerebral oxygenation in health and disease - Niels H. Secher (Frontiers Research Topics, 2015)
Scientists and clinicians interested in cerebrovascular physiology in humans now have numerous possibilities to monitor, invasively or non-invasively, the oxygenation status of cerebral tissue. Monitoring cerebral oxygenation has several utilities; to improve patient outcome, to better understand the mechanisms underlying orthostatic hypotension; to provide insight into functional neurovascular coupling; to evaluate the influence of vasopressors on cerebral oxygen levels in patients under anesthesia; and to study the limitations of exercise tolerance. This themed research topic, through theoretical and experimental papers, covers new and exciting issues related to the study of cerebral oxygenation in health and disease. This e-book includes manuscripts inclusive of original research, methodologies and reviews in the field of integrative physiology, cognitive testing, orthostatic stress, exercise physiology and anesthesia.